Pharmacokinetic Evaluation of a Novel Donepezil-Loaded Dissolving Microneedle Patch in Rats - Naveed Ur Rehman; Chanwoo Song; Junhyeong Kim; Inhwan Noh; Yun-Seok Rhee; Hye Jin Chung (MDPI AG, 2021)
Research on the development of dissolving microneedles (DMNs) has focused on bolus drug delivery, with little attention on sustained release. Here, we evaluated the sustained release, absorption pattern, and effective drug permeation of a novel donepezil-loaded DMN patch through an in vivo investigation on rats. The applications of DMN patches to the shaved skin of rats for 1 week and 1 h were compared with oral donepezil administration to assess their sustained release capabilities. We used a validated liquid chromatography-tandem mass spectrometry method to quantify donepezil in the plasma. We found that the microneedle arrays effectively delivered donepezil across the skin, with dissolution observed within 1 h of application. Furthermore, skin irritation test showed that the patches produced no irritation response. The DMN arrays also effectively increased drug permeation and demonstrated sustained release and absorption of donepezil from DMN patches. These patches allow extended dosing intervals, reduced gastrointestinal adverse effects, and convenient self-administration to mitigate poor drug compliance, making them beneficial for the treatment of elderly patients with Alzheimer's disease.